Димензиите и карактеристиката на сивата економија во Република Македонија - Садику, Лулјета (Економски факултет, УКИМ, Скопје, 2015)
Grey economy relates to the problem of non-reporting and/or underreporting of market transactions by economic agents. The prevalence of grey economy can have serious impact on economic growth as well as income distribution in a country. Findings and perceptions of the existing sources suggest decline of the grey economy in Macedonia. Thus, the main purpose of this paper is to rigorously estimate the size of grey economy in RM and reconcile the perception with observed facts and with the latest data, covering the period 1998Q1-2014Q1. To estimate the size of the grey economy, we use the indirect method of monetary approach involving an econometric estimation of the demand for currency, and the multiple causes multiple indicators (MIMIC) approach. Results of both approaches show that the grey economy of Macedonia varies between 48%-29% of the official GDP, reaching very high levels in the period 1998Q1-2001Q4 and showing a slightly decreasing trend since then. The last period of 2010Q1-2014Q1 shows a rapid decline in the magnitude of the grey economy compared with the previous periods, with the size of the grey economy falling to about 29 percent of official GDP. Furthermore, the research confirms a negative relationship between grey economy and formal economy, ie for 1% increase of grey economy, the formal economy decreases by 0.09%. The decreased tax burden, the improved regulatory quality and the increased formal employment go far to explain the reduction in the size of the grey economy in recent years. We find that the high levels of unemployment, the low standards of living for the most of society, the high level of bribery and corruption remain the main factors that continue to lie at the root of the grey economy in the Republic of Macedonia.
Dimensions and characteristics of the grey economy in the Republic of Macedonia
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: grey economy, monetary approach, MIMIC approach, currency demand, formal economy